Design and development of mobile application for academic reminder system / Nik Ruslawati Nik Mustapa and Siti Hajar Natasha Mustapa - Nik Mustapa, Nik Ruslawati; Mustapa, Siti Hajar Natasha (UiTM Cawangan Perlis, 2020)
The Academic Reminder System is built to help users, which focuses for the students in UiTM Tapah to manage their scheduled class and assignment deadline via their mobile smartphones. The application was built for android-based platform. The user only needs to update their schedule after getting logged into the system and list any important date for their assignment deadline to the system. Then, the system will give an alert to remind the user for the upcoming class and task deadline. The System Development Life Cycle (SDLC) which is the waterfall model has been chosen as the methodology for this project that containing five phases. The result of the discussion shows that Academic Reminder System receives positive feedback through usability testing that has been completed. A total 30 students completed the usability survey and 46.7% of respondent are strongly agreed that this application meets their satisfaction with interface, usability, and performance. Future work recommendation for this project is to make a sharing application tool in the system so that the user can simply share the application to their friends. Besides that, the application can engage with new technology, which is using near-field communication (NFC) in the log in page to easier for students log into the system.